Beneficial soil microbiome profiles assembled using tetramycin to alleviate root rot disease in Panax notoginseng - Liu, Lianjin; Wang, Zongqing; Luo, Cheng; Deng, Yinglong; Wu, Wentao; Jin, Yongping; Wang, Yuxuan; Huang, Hongping; Wei, Zhaoxia; Zhu, Youyong; He, Xiahong; Guo, Liwei (Frontiers in Microbiology, 2025)
BackgroundRoot rot disease is a major threat to the sustainable production of Panax notoginseng. Tetramycin has a broad-spectrum fungicidal efficacy, low toxicity, and high efficiency, However, the prevention and control of root rot disease of P. notoginseng and the specific mechanism of action are still unclear.MethodsIn this paper, a combination of indoor and pot experiments was used to assess the effectiveness of tetramycin at alleviating root rot disease challenges encountered by P. notoginseng. Amplicon sequencing, metagenomic analysis with microbial verification were used to investigate the microecological mechanisms underlying tetramycin’s ability to reduce soil biological barriers.ResultsWe found that tetramycin significantly inhibited mycelial growth and spore germination of pathogenic fungi. Tetramycin, T2 (1000×) and T3 (500×), applied to continuous cropping soil, increased the seedling survival rates of P. notoginseng. Additionally, tetramycin reduced fungal α-diversity and shifted the fungal community assembly from deterministic to stochastic process. The microbial functions influenced by tetramycin were primarily associated with antibiotic synthesis and siderophore synthesis. Antibiotic efflux and inactivation have also been identified as the main resistance mechanisms. Microbial verification results showed that the artificially assembled tetramycin-regulated microbial community could indeed alleviate the occurrence of diseases. Furthermore, the cross-kingdom synthetic community assembled by the three key strains (Pseudomonas aeruginosa, Variovorax boronicumulans, and Cladosporium cycadicola) significantly improved the control of root rot disease and promoted plant growth.DiscussionThis study provides novel insights into developing efficient biological control strategies and elucidates the role and mechanism of tetramycin in modulating soil microflora assembly to strengthen host disease resistance.